Love thy Neighbour… or not: Christians, but not Atheists, Show High In-Group Favoritism. (17th June 2021) - Speed, David; Brewster, Melanie
Atheists are among the most disliked groups in America, which has been explained in a variety of ways, one of which is that atheists are hostile towards religion and that anti-atheist prejudice is therefore reactive. We tested this hypothesis by using the 2018 American General Social Survey by investigating attitudes towards atheists, Christians, Buddhists, Hindus, Jews, and Muslims. We initially used a general sample of Americans, but then identified and isolated individuals who were atheists, theists, nonreligious atheists, religious theists, and/or theistic Christians. Logically, if atheists were inordinately hostile towards religion, we would expect to see a greater degree of in-group favouritism in the atheist group and a greater degree of out-group dislike. Results indicated several notable findings: 1). Atheists were significantly more disliked than any other religious group. 2). Atheists rated Christians, Buddhists, Jews, and Hindus as favourably as they rated their own atheist in-group, but rated Muslims less positively (although this effect was small). 3). Christian theists showed pronounced in-group favouritism and a strong dislike towards atheists. No evidence could be found to support the contention that atheists are hostile towards religious groups in general, and towards Christians specifically, although this may have been a Type II error. If atheist groups do dislike religious groups, then this hypothetical dislike would be significantly smaller in magnitude than the dislike directed toward atheists by Christians.